EBR and JA regulate aroma substance biosynthesis in ‘Ruidu Hongyu’ grapevine berries by transcriptome and metabolite combined analysis - Li, Jiajia; Quan, Yi; Wu, Zishu; Han, Jiayu; Zhang, Ying; Javed, Hafiz Umer; Ma, Chao; Jiu, Songtao; Zhang, Caixi; Wang, Lei; Wang, Shiping (Frontiers in Plant Science, 2023)
Volatile compounds including terpenes, aldehyde, phenol, and alcohol are significantly contributed floral and fruity aromas to the Muscat variety. ‘Ruidu Hongyu’ grapevine is one of the newly developed grape varieties, and cultivation of this variety has been extended across China due to unique quality traits and taste. In this study, HS-SPME/GC‒MS and transcriptome sequencing analysis were performed to evaluate the impact of exogenous 2,4-epibrassinolide (EBR), jasmonic acid (JA), and their signaling inhibitors brassinazole (Brz)/sodium diethyldithiocarbamate (DIECA) on the biosynthesis of aroma substances in ‘Ruidu Hongyu’ grapevine. According to the results, exogenous BR and JA promoted the accumulation of various aroma substances, including hexenal, 2-hexenal, nerol oxide, vanillin, hotrienol, terpineol, neral, nerol, geraniol, and geranic acid. After EBR and JA treatments, most of the genes responsible for terpene, aldehyde, and alcohol biosynthesis expressed at a higher level than the CK group. Relatively, EBR treatment could not only promote endogenous BR biosynthesis and metabolism but also elevate BR signaling transduction. JA treatment contributed to endogenous JA and MeJA accumulation, as well. Through transcriptome sequencing, a total of 3043, 903, 1470, and 607 DEGs were identified in JA vs. JD, JA vs. CK, BR vs. CK, and BR vs. Brz, respectively. There were more DEGs under both EBR and JA treatments at late fruit ripening stages. The findings of this study increase our understanding regarding aroma substances biosynthesis and endogenous BR/JA metabolism in response to exogenous EBR and JA signals.